Investigating The Relationship Between Fdi Inflows And Economic Recovery In Selected Conflict-Affected And Fragile States - Anthony Oyamendan; Babatunde Afolabi; Debo-Ajagunna Adebolanle; Olaoluwa Omotayo Olanipon; Egunlusi Femi Bamidele (Journal of Business and Management Inaba, 2025)
This study examined the connection between economic recovery and foreign direct investment (FDI) inflows in a few conflict-affected and fragile states: Yemen, Somalia, South Sudan, Afghanistan, and the Democratic Republic of the Congo (DRC) between 2010 and 2022. It investigates how FDI interacts with conflict intensity and institutional quality to shape recovery trajectories, drawing on modernization theory and conflict economics. The study uses panel regression techniques alongside qualitative insights derived from interviews and observations to evaluate the effects of conflict intensity (deaths from battle), institutional quality (governance indicators), and foreign direct investment (FDI) (as a percentage of GDP) on real GDP per capita growth. It employs an ex-post facto research design and utilizes secondary data from the World Bank, UNCTAD, and ACLED. According to descriptive research, FDI inflows are moderate and erratic, averaging 1.85% of GDP, and are mostly concentrated in extractive industries with little impact on employment. Furthermore, institutional quality has a marginally significant beneficial impact on recovery, but foreign direct investment has a negative but statistically negligible effect. The consistently large positive link between conflict intensity and economic recovery shows the growth effects of aid and rebuilding flows during war episodes. Overall, the results indicate that capital investment and rebuilding dynamics are more important for recovery in fragile nations than foreign direct investment (FDI), with poor institutions limiting the transformative potential of FDI. Recommendations include enhancing governance and judiciously allocating FDI to promote productivity, inclusive growth, and technology transfer.